Rancang Bangun Sistem Rekomendasi Pemilihan Smartphone Berbasis Web - Adhi Kusnadi; Christophorus Kris Widiarso; Hugeng Hugeng (Universitas Multimedia Nusantara, 2016)
With so many variations in the number of smartphones in the market makes it difficult to choose. Therefore, it is necessary to make a recommendation system that can help the process of selecting a smartphone. For the system of recommendation used the method weihgted product. Weighted product method is a method frequently used in the Multi- Criteria Decision Making. Weighted product method capable of finding the best sequence of several alternatives, with criteria price, size, type of OS, RAM size, processor speed, storage capacity, the ability of photography, and the battery capacity. To test user satisfaction is conducted survey of 30 respondents, with Likert scale and Cronbach Alpha. The figures obtained was 0.70, indicating that the system got quite good feedback from respondents. Keywords - recomended system, smartphones, weighted product.